Установка для получения поликристаллического кремния - Гаврилов П. М. Петр Михайлович; Бараков Б. Н. Борис Николаевич; Муравицкий С. А. Степан Александрович; Никулин А. И. Анатолий Иванович; Прочанкин А. П. Александр Петрович; Ревенко Ю. А. Юрий Александрович
опубл. 27.09.08